Effectiveness of acoustic AR-TA agent using localised footsteps corresponding to audience members' participating attitudes. (7th January 2021) - Kitagishi, Yuki; Yonezawa, Tomoko
We investigated an acoustic augmented reality teaching assistant agent (AATA) that walks according to the participating attitudes of the audience members in one-to-many communications. If participants are not focused on the lecture, it is difficult to make them pay attention. To improve such audience members' attitudes, or to draw their attention to the appropriate target, we propose an AATA expressed by moving the localised footsteps using a direction-controllable parametric speaker. We conducted the experiment to evaluate the effectiveness of the AATA. As the results, the participants felt as though someone, the teaching assistant or the lecturer, was walking around them when they perceived the movement of the localised footsteps, and they felt the changes in the AATA's attention and intention to them when the AATA's walking pattern was changed. Accordingly, it is proposed that the AATA's movement can deliver an implicit message to the audience members.